Intimate Partner Violence and Associated Risk Factors Among Youth in the Slums of Kampala - Culbreth, Rachel (Journal of interpersonal violence, 2021)
The purpose of this study is to examine the factors associated with intimate partner violence (IPV) among youth living in the slums of Kampala. This analysis is based on a cross-sectional study of youth living in the slums of Kampala conducted in spring 2014 (N = 1,134). The participants (12–18 years of age) were attending Uganda Youth Development Link centers, which serve youth living on the streets and slums of Kampala. Bivariate and multivariable multinomial analyses were conducted to examine risk factors associated with IPV victimization only, IPV perpetration only, and both IPV victimization and perpetration compared with no IPV victimization or perpetration. Among youth who reported having a boyfriend or girlfriend (n = 600), 18.3% (n = 110) reported experiencing both IPV victimization and perpetration, 11.0% (n = 66) reported IPV perpetration only, 7.7% (n = 46) reported experiencing IPV victimization only, and 63.0% (n = 378) reported no IPV experiences. In the multivariable analysis, IPV victimization only was associated with witnessing parental IPV (odds ratio [OR] = 2.78; 95% confidence interval [CI] = [1.42, 5.48]), experiencing parental physical abuse (OR = 2.27; 95% CI = [1.16, 4.46]), and neighborhood cohesiveness (OR = 0.73; 95% CI = [0.31, 1.69]). IPV perpetration was only associated with experiencing parental physical abuse (OR = 2.86; 95% CI = [1.62, 5.07]). Reporting both IPV victimization and perpetration was associated with non-problem drinking (OR = 2.03; 95% CI = [1.15, 3.57]), problem drinking (OR = 2.65; 95% CI = [1.48, 4.74]), witnessing parental IPV (OR = 2.94; 95% CI = [1.80, 4.80]), experiencing parental physical abuse (OR = 2.23; 95% CI = [1.38, 3.60]), and homelessness (OR = 1.90; 95% CI = [1.14, 3.16]). Levels of IPV victimization and perpetration are very high in this population and warrant urgent attention.